PEMBELAJARAN INTERDISIPLIN DI SEKOLAH DASAR (JS (JURNAL SEKOLAH), 2020)
Abstract: The 2013 curriculum, which emphasizes integrated thematic learning, is actually a reflection of interdisciplinary learning because it combines several scientific disciplines, such as mathematics, language, science, and natural sciences, into a theme. Therefore, the author, on this occasion, tries to discuss how interdisciplinary learning between mathematics and other fields of science is presented. First, the author discusses interdisciplinary learning between mathematics and music and dance, and then it is followed by interdisciplinary learning between mathematics and literacy presented in mathematics picture books. Third, the author discusses the interdisciplinary learning between rock climbing and mathematics, and finally this paper discusses STEM or STEAM learning. The implication of interdisciplinary learning in elementary schools is that teachers need to collaborate to create creative, innovative, and fun learning activities.Keywords: Interdisiplinarity, mathematics, music and dance, math picture books, sport, STEAMAbstrak: Kurikulum 2013 yang menekankan pada pembelajaran tematik terpadu sesungguhnya merupakan cerminan dari pembelajaran interdisiplin karena menggabungkan beberapa disiplin ilmu, seperti matematika, bahasa, sains, dan ilmu pengetahuan alam, kedalam sebuah tema. Oleh karena itu, penulis pada kesempatan ini mencoba mendiskusikan bagaiaman pembelajaran interdisiplin antara matematika dengan berbagai bidang ilmu lainnya dari berbagai literatur. Pertama yang akan dibahas yaitu pembelajaran interdisplin antara matematika dan seni musik dan tari, kemudian dilanjutkan dengan pembelajaran interdisiplin antara matemetika dan literasi yang tertuang dalam buku bergambar matematika. Ketiga, penulis mendiskusikan pembelajaran yang mengabungkan antara oleh raga panjat tebing, dengan matematika, dan terakhir dibahas tentang pembelajaran STEM atau STEAM. Implikasi dari pembelajaran interdisiplin di sekolah dasar yaitu mengharuskan guru-guru untuk berkolaborasi guna menciptakan aktivitas pembelajaran yang kreatif, inovatif, dan menyenangkan.Kata Kunci: Interdisiplinarity, matematika, seni musik dan tari, math picture books, olahraga, STEAM